Age Effects on Neural Discriminability and Monitoring Process During Memory Retrieval for Auditory Words - Shao, Xuhao; Liu, Wenzhi; Guo, Ying; Zhu, Bi (Frontiers in Aging Neuroscience, 2022)
After hearing a list of words (e.g., dream, awake, and bed), older adults tended to have more difficulty than younger adults in distinguishing targets (e.g., dream) from lures (e.g., sleep) and foils (e.g., pen) in a visual recognition test. Age-related reduction in neural discriminability in the visual cortex has been linked to deficits in memory discriminability of pictures. However, no study has examined age differences in auditory discrimination and prefrontal monitoring during true and false memory retrieval after hearing words. The current study used a visual recognition test following an auditory study of words, and showed that older adults had lower true recognition and higher propensity for high-confidence false recognition compared to young adults. Using classification-based multivariate pattern analysis for functional neuroimaging data during memory retrieval, we found that neural activation patterns in the primary auditory cortex could be used to distinguish between auditorily-studied targets and unstudied lures in young adults, but not in older adults. Moreover, prefrontal monitoring for lures was weaker in older adults as compared to young adults. Individual differences analysis showed that neural discriminability in the primary auditory cortex was positively related to true recognition, whereas prefrontal activation for lures was negatively related to the propensity for high-confidence false recognition in young adults but not in older adults. Together, age differences in true and false memories following auditory study are associated with reduced neural discriminability in the primary auditory cortex and reduced prefrontal monitoring during retrieval.